المسكوت عنه في الرواية العربية - الكتابة النسائية أنموذجا - مصباحي, خولة (جامعة الوادي - University of Eloued, 2020)
تناول هذا البحث تقنية المسكوت عنه في السرد الروائي ويختار الرواية النسائية مجالا للدرس، خاصة بعد القفزة التي حققها السرد النسائي بتخطيه عوالم المعتاد والمفروض وبحثه في الممنوع والمحظور ونبشه في المضمر والمسكوت عنه. وقام معمار هذا البحث على تمهيد طرحنا فيه إشكالية المسكوت عنه في الكتابة النسائية وفصلين حمل الأول عنوان: الرواية النسائية وإستراتيجية خرق الثالوث المحرم(السياسة، الدين، الجنس)، ودرء لأي إطناب أو تشتت في الأفكار آثرنا أن نقصر اهتمامنا في أحد جوانب الثالوث المحرم (الجنس) فكان هذا هو محتوى الفصل الثاني والذي وسم بـــ: أزمة الجنس وتشكيلات الجسد. وفي ختام البحث تم التوصل إلى جملة من النتائج من أهمها كيف عالجت الرواية النسائية التابوهات، وكيف وظفتها في محكيها مزاوجة بين الحضور الجمالي والمحظور القرائي. : Abstract This research deals with the technique of the masked narrator in the narration of the novel .It chooses the women's story as a field of study, especially afterThis research deals with the technique of the masked narrator in the narration of the novel .It chooses the women's story as a field of study, especially after the leap achieved by the narrative of women by crossing the worlds usual, imposed and discussed the forbidden, prohibited and even the hidden in the implicit and silent about it (politics, religion and sex). In order to avoid any exaggeration or dispersion of ideas, we preferred to focus on the side of the forbidden Trinity (sex). This was the content of the second chapter Which is characterized by the crisis of sex and body formations .At the end of the research, a number of results were reached, the most important of which were how the women's story dealt with the taboos, and how they were used in their narration to match the aesthetic and the forbidden reading.
The Unsaid In Arabs Novels Women 's Writing As A Study Case
مقال
Keywords: الكتابة النسائية ؛ المسكوت عنه ؛ الثالوث المحرم ؛ الكتابة بالجسد; women's writing; silent about it; forbidden trinity